Marginal malnutrition and intellectual development in Cali schoolchildren (Colombia Medica, 1986)
It was attempted to show whether marginal malnutrition, mother's education, number of children in the family, and birth order were related to mental development in a selected group of 99 male students (aged 6-16 years) from public schools in low-income neighborhoods in Cali, Colombia. The Rueda-Williamson standards for Colombian children were used for nutritional classification, where the normal group consisted of boys whose weight was between 95 and 110% of expected weight for age and height, and the low weight group included boys who weighed less than 95% of the standard for age and for height. Intellectual development was evaluated utilizing the Goodenough-Harris drawing test and the Raven's progressive matrices test. A consistent tendency for lower performance in the low-weight group was found, with differences reaching statistical significance in the Goodenough-Harris drawing test. No associations were found between mental development and the mother's education, the number of children in the family, and birth order.